Knowledge Level About Osteoporosis and Risk Factors Prevalance Among Women With The Age of 40 Years and Over; and Among Female Teachers in Some Schools in Two Regions of Ankara - Sabahat Tezcan; Nuket Subaşı; Hakan Altıntaş (Galenos Yayinevi, 2002)
The aim of this review is to ascertain the osteoporosis risk factors and the knowledge level of women about osteoporosis which were obtained from three studies conducted with women; and submitting these data to the attention of authorities while providing new data to the existing research and data on osteoporosis. 600 women from two health center regions (study I), 170 female teachers from two schools in the same region (study II) and 80 female teachers from a preliminary school (study III) participated in the study. In the first study, while 16.2% of the women had no risk of osteoporosis, 40.8% of them had 1-2, 6.6% of them has 5 or more risk factors. In the second study, there was nobody who had no risk of osteoporosis. While 50.0% of them had 3-4, 44.7% of them had 5 or more risk factors. In the third study, there is nobody who had no risk of osteoporosis. 9.6% of them had 5 or more risk factors. 86.2% of the women in the first study, and 7.5% of teachers in second study had no information about the definition of osteoporosis. The cause of osteoporosis was not known by 34.7% of the women in the first, and 13.6% of the teachers in the second study. The diagnostic methods of osteoporosis were not known by 57.0% of the women in the first and %37.2 of the teachers in the second study. The main information source was television in both studies, health professionals were on the third rank in both groups.The support of visional media is definite on the health education about osteoporosis, but it is thought that the health professionals, who are the main information source, need to be more involved in such education.